1998
DOI: 10.1029/98jd01564
|View full text |Cite
|
Sign up to set email alerts
|

A multilayer model for inferring dry deposition using standard meteorological measurements

Abstract: Abstract. In this paper, we describe the latest version of the dry deposition inferential model, which is used to estimate the deposition velocities (V a) for SO2, 03, HNO3, and particles with diameters less than 2 •m. The dry deposition networks operated by the National Oceanic and Atmospheric Administration (NOAA) and the Environmental Protection Agency (EPA) use this model to estimate dry deposition on a weekly basis. This model uses a multilayer approach, discretizing the vegetated canopy into 20 layers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(182 citation statements)
references
References 47 publications
(13 reference statements)
5
175
0
1
Order By: Relevance
“…The first scenario takes the measured Candor CASTNet concentration as a proxy for Duke Forest and calculates HNO 3 fluxes using a resistance-based multilayer model (MLM; Meyers et al, 1998) to produce weekly estimates of dry deposition as described by Clarke et al (1997). A comparison of concentration estimates using ADS during the CELTIC study at Duke Forest and filter packs from the Candor CASTNet site suggested a possible bias in the partitioning between HNO 3 and NO 3 À (Table 3) in the CASTNet data.…”
Section: Scaling To Annual Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The first scenario takes the measured Candor CASTNet concentration as a proxy for Duke Forest and calculates HNO 3 fluxes using a resistance-based multilayer model (MLM; Meyers et al, 1998) to produce weekly estimates of dry deposition as described by Clarke et al (1997). A comparison of concentration estimates using ADS during the CELTIC study at Duke Forest and filter packs from the Candor CASTNet site suggested a possible bias in the partitioning between HNO 3 and NO 3 À (Table 3) in the CASTNet data.…”
Section: Scaling To Annual Estimatesmentioning
confidence: 99%
“…This is primarily due to the difficulty in achieving acceptable precision at short sampling times required by traditional micrometeorological flux measurement techniques. We have, therefore, estimated fluxes of NH 3 , NH 4 1 , HNO 3 , and NO 3 À using a combination of measurements and modeling, which is a common approach when only routine chemical and meteorological data are available (Meyers et al, 1998;US EPA, 2004). Only chemical and meteorological measurements taken above the canopy were used to estimate dry deposition fluxes from the model simulation.…”
Section: Long-term Data Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, if information about the vegetation morphology (e.g., canopy height (h c ), and LAI) is known, z 0 can be calculated following Meyers et al (1998): z 0 ¼ h c 0:215 À LAI 0:25 10 ;…”
Section: Evaluation Of Modeled V D (No Y )mentioning
confidence: 99%
“…Wesely, 1989;Meyers et al, 1998;Zhang et al, 2002Zhang et al, , 2003Niyogi et al, 2009;Wu et al, 2003) to estimate the dry deposition velocity (V d ) by commonly utilizing the resistance approach analogous to Ohm's law in electrical circuits. Accurately parameterizing the complex surfaceatmosphere exchange process remains challenging for V d modeling due to large variability in surface conditions (e.g., vegetation types, and soil contents) at model sub-grid scales.…”
Section: Introductionmentioning
confidence: 99%